2022
DOI: 10.3390/app12031103
|View full text |Cite
|
Sign up to set email alerts
|

Packet Injection Exploiting Attack and Mitigation in Software-Defined Networks

Abstract: Software-defined networking (SDN) decouples the control plane and data plane through OpenFlow technology and allows flexible network control. It has been widely applied in different areas and has become a focus of attention in the future network. With SDN’s development, its security problem has become a necessary point of research to be solved urgently. In this paper, we propose a novel attack, namely, the packet injection exploiting attack. By maliciously injecting false hosts into SDN network topology, attac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…To detect packet injection attacks on SDN, Jishuai et al [26] added a new component (PIEDefender) to an SDN controller. This add-on is protocol-independent and does not require any additional hardware.…”
Section: Packet Injection Attacks On Sdnmentioning
confidence: 99%
See 1 more Smart Citation
“…To detect packet injection attacks on SDN, Jishuai et al [26] added a new component (PIEDefender) to an SDN controller. This add-on is protocol-independent and does not require any additional hardware.…”
Section: Packet Injection Attacks On Sdnmentioning
confidence: 99%
“…It was found that this add-on enabled the controller to detect packet injection attacks with 97.8% precision. Unlike [26], our approach does not add any component to the controller but incorporates deep learning to detect packet injection attacks.…”
Section: Packet Injection Attacks On Sdnmentioning
confidence: 99%